BACK and DRAW activities for improving writing skills - Syafii, Muhammad Lukman (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2017)
This present paper addresses the issue of writing as an important aspect of EFL instruction. Writing as one of the four basic language skills plays a pivotal role in the context of English teaching as a foreign language in Indonesia. Considering these problems, it is important to modify the writing process in such a way to cope the writing. The process of writing the writer means is BACK and DRAW activities. What the writer termed as BACK and DRAW is a set of writing activities involving studentsâ active participation in the process, their intense learning experience in producing a required text, as well as their interactive work with peers and the teacher. BACK and DRAW stands for Brainstorming, Attaching, Correcting, Keeping, Developing, Revising, Arranging, and Wow! Or Wonderful! Or Well done!. These activities are good ways to improve the writing Ability.